ANALISIS KEJADIAN ANEMIA PADA IBU HAMIL DI UPTD PUSKESMAS KOTA BATURAJA KABUPATEN OKU - Retno Widiastuti; Ferly Oktiyedi; Rico Januar Sitorus (MOTORIK Jurnal Ilmu Kesehatan, 2023)
Mother and children are family members need to get priority in the implementation of. health efforts Anemia affect pregnant women by 40 %. Type this research is designed observational analytic cross sectional study. Baturaja this study was conducted in the province of south sumatra in june 2022. Population this is pregnant women in research in the city the publisch health district Baturaja, OKU march 2022 flattened the were the 200. The technique was used in the study of the receipt of the samples to total the sampling method of by using 200 respondents pregnant women of 4 publich health in the city Baturaja. There was a correlation meaningful statistically between education with the genesis anemia for pregnant women (p-value 0,000), economic status (p-value 0,000), consumption tablet Fe (p-value 0,000), and the inspection for non-nakes (p- value 0,000). Needs to enhance monitoring, early detection, counseling information and education about risk factors anemia for pregnant women.